Purinergic signalling in systemic sclerosis - Hoeppner, Jakob; Bruni, Cosimo; Distler, Oliver; Robson, Simon C.; Burmester, Gerd R.; Siegert, Elise; Distler, Jörg (Rheumatology, 2021)
SSc is a chronic autoimmune rheumatic disease that involves numerous organs and presents major management challenges. The histopathologic hallmarks of SSc include vasculopathy, fibrosis and autoimmune phenomena involving both innate and adaptive immune systems. Purinergic signalling is a pathway that may be implicated in the pathophysiology of several of these disease manifestations. Extracellular purines are potent signalling mediators, which have been shown to be dysregulated in SSc. As examples, purines can exacerbate vasculopathy and provoke platelet dysfunction; as well as contributing to immune dysregulation. Elements of purinergic signalling further promote organ and tissue fibrosis in several disease models. Here, we provide an overview of extracellular purine metabolism in purinergic signalling and link disorders of these to the molecular pathology of SSc. We also discuss targeting the purinergic signalling and explore the translational applications for new therapeutic options in SSc.
CRIS-Team WoS Importer:2022-05-13